Cytosolic phospholipase A2α regulates G1 progression through modulating FOXO1 activity. Issue 3 (7th December 2015) - Naini, Said Movahedi; Choukroun, Gabriel J.; Ryan, James R.; Hentschel, Dirk M.; Shah, Jagesh V.; Bonventre, Joseph V.
Abstract : Group IVA phospholipase A2 [cytosolic phospholipase A2 α (cPLA2 α)] is a key mediator of inflammation and tumorigenesis. In this study, by using a combination of chemical inhibition and genetic approaches in zebrafish and murine cells, we identify a mechanism by which cPLA2 α promotes cell proliferation. We identified 2 cpla2 α genes in zebrafish, cpla2 αa and cpla2 αb, with conserved phospholipase activity. In zebrafish, loss of cpla2 α expression or inhibition of cpla2 α activity diminished G1 progression through the cell cycle. This phenotype was also seen in both mouse embryonic fibroblasts and mesangial cells. G1 progression was rescued by the addition of arachidonic acid or prostaglandin E2 (PGE2 ), indicating a phospholipase‐dependent mechanism. We further show that PGE2, through PI3K/AKT activation, promoted Forkhead box protein O1 (FOXO1) phosphorylation and FOXO1 nuclear export. This led to up‐regulation of cyclin D1 and down‐regulation of p27 Kip1, thus promoting G1 progression. Finally, using pharmacologic inhibitors, we show that cPLA2 α, rapidly accelerated fibrosarcoma (RAF) /MEK/ERK, and PI3K/AKT signaling pathways cooperatively regulate G1 progression in response to platelet‐derived growth factor stimulation. In summary, these data indicate that cPLA2 α, through its phospholipase activity, is a critical effector of G1 phase progression through the cell cycle and suggest that pharmacological targeting of this enzyme may have important therapeutic benefits in disease mechanisms that involve excessive cell proliferation, in particular, cancer and proliferative glomerulopathies.—Naini, S. M., Choukroun, G. J., Ryan, J. R., Hentschel, D. M., Shah, J. V., Bonventre, J. V., Cytosolic phospholipase A2α regulates G1 progression through modulating FOXO1 activity. FASEB J. 30, 1155–1170 (2016). www.fasebj.org